Impaired Channel Targeting and Retinal Degeneration in Mice Lacking the Cyclic Nucleotide-Gated Channel Subunit CNGB1 - Hüttl, Sabine (Society for Neuroscience, 2005)
Cyclic nucleotide-gated (CNG) channels are important mediators in the transduction pathways of rod and cone photoreceptors. Native CNG channels are heterotetramers composed of homologous A and B subunits. In heterologous expression systems, B subunits alone cannot form functional CNG channels, but they confer a number of channel properties when coexpressed with A subunits. To investigate the importance of the CNGB subunits in vivo, we deleted the CNGB1 gene in mice. In the absence of CNGB1, only trace amounts of the CNGA1 subunit were found on the rod outer segment. As a consequence, the vast majority of isolated rod photoreceptors in mice lacking CNGB1 (CNGB1(-/-)) failed to respond to light. In electroretinograms (ERGs), CNGB1(-/-) mice showed no rod-mediated responses. The rods also showed a slow-progressing degeneration caused by apoptotic death and concurred by retinal gliosis. Cones were primarily unaffected and showed normal ERG responses up to 6 months, but they started to degenerate in later stages. At the age of ∼1 year, CNGB1(-/-) animals were devoid of both rods and cones. Our results show that CNGB1 is a crucial determinant of native CNG channel targeting. As a result of the lack of rod CNG channels, CNGB1(-/-) mice develop a retinal degeneration that resembles human retinitis pigmentosa.